Residual relief modelling: digital elevation enhancement for shipwreck site characterisation - Jan Majcher; Ruth Plets; Rory Quinn (Archaeological and Anthropological Sciences, 2020)
Scour processes play a critical role in the preservation status of submerged historic shipwrecks. Erosion of sediment leads to enhanced exposure of archaeological sites to physical, chemical and biological processes. Current methods for identifying erosional and depositional features at wreck sites are based primarily on visual interpretation of data, which is labour-intensive and entirely subjective. The increasing availability of high-resolution multibeam echosounder–derived digital elevation models (DEMs) of historic wreck sites allows for an entirely new level of detailed interrogation and analyses of the geomorphological features associated with these. In this study, we present a residual relief modelling method for the semi-automated extraction of such depositional and erosional features at wreck sites. Relief modelling is supplemented with a breakpoint classification approach, with final separation supported by DEM visualisation enhancement techniques. We applied the method to three World War I shipwreck sites and evaluated it against traditional manual vectorisation techniques. The results suggest that the semi-automated modelling method is robust, time-effective and capable of quantifying the products of scour processes with increased objectivity. Our method holds great potential for the objective characterisation of erosional and depositional patterns and processes at wreck sites, which have important implications for site formation studies and in situ preservation of underwater cultural heritage.